2008
DOI: 10.1007/s00787-008-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character among Korean children and adolescents with anxiety disorders

Abstract: The purpose of this study was to evaluate the temperament and character of children and adolescents with anxiety disorders in samples from Korean community. The study subjects were children and adolescents diagnosed with social phobia (n = 66), separation anxiety disorder (n = 47), specific phobia (n = 415), and obsessive-compulsive disorder (n = 42) with the diagnostic interview schedule for children, version IV (DISC-IV) in representative community samples. Among these, we excluded other psychiatric disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Investigating life events and personality factors with obsessive-compulsive disorder and anxiety disorders in a trilateral comparison (patients with anxiety disorder, OCD and normal subjects), Gothelf et al [17], comparing children with anxiety disorder with OCD children, did not find life events and HA to play a distinguishing role. In a very similar study to ours Cho et al [4] compared the JTCI temperament profiles of 4 distinct anxiety disorders and found HA predictive in both social phobia and specific phobia, while subjects with both social phobia and obsessive-compulsive disorder indicated lower means in self directedness. Social phobic adolescents enjoy some defense against risky influences, as their avoidance from peers yields a relative uninolvement in dangerous activities.…”
Section: Discussionsupporting
confidence: 58%
“…Investigating life events and personality factors with obsessive-compulsive disorder and anxiety disorders in a trilateral comparison (patients with anxiety disorder, OCD and normal subjects), Gothelf et al [17], comparing children with anxiety disorder with OCD children, did not find life events and HA to play a distinguishing role. In a very similar study to ours Cho et al [4] compared the JTCI temperament profiles of 4 distinct anxiety disorders and found HA predictive in both social phobia and specific phobia, while subjects with both social phobia and obsessive-compulsive disorder indicated lower means in self directedness. Social phobic adolescents enjoy some defense against risky influences, as their avoidance from peers yields a relative uninolvement in dangerous activities.…”
Section: Discussionsupporting
confidence: 58%
“…found in anxious adults and children, who initially gaze more at threatening pictures than non-anxious adults and children (vigilance), but subsequently gaze less at them than nonanxious adults and children (avoidance) (In-Albon et al, 2010). A Korean study (Soo-churl et al, 2009) evaluated temperament and character of children and adolescents with anxiety disorders, in part subjects with separation anxiety, using the Junior Temperament and Character Inventory (JTCI). Separation anxiety disorder was not associated with any temperament and character on the JTCI, opposite to others anxiety diagnosis.…”
Section: The Risk Factors and Background Of The Separation Anxietymentioning
confidence: 99%
“…Separation anxiety disorder was not associated with any temperament and character on the JTCI, opposite to others anxiety diagnosis. Children and adolescents with anxiety disorders could have different temperaments and character profiles in accordance with diagnostic groups, which imply the specific pathophysiological mechanism of each anxiety disorder (Soo-churl et al, 2009). …”
Section: The Risk Factors and Background Of The Separation Anxietymentioning
confidence: 99%
“…For example, using the JTCI, children with Attention Deficit Hyperactivity Disorder (ADHD) and sub-threshold ADHD have a profile of high novelty seeking, low persistence, and low self-directedness (SD), when compared with those of a control group. In addition, application of JTCI29,35 has shown that children and adolescents with social phobias have a profile of high harm avoidance and low SD.…”
Section: Introductionmentioning
confidence: 99%